Ectodermal dysplasia treated with one step surgical rehabilitation: a case report - Grecchi, Francesco; Pricolo, Alfonso; Parafioriti, Antonina; Mineo, Giuseppe; Zollino, Ilaria; Carinci, Francesco (Journal of Osseointegration, 2010)
Ectodermal dysplasia (ED) comprises a large, heterogeneous group of inherited disorders that are defined by primary defects in the skin, hair, nails, eccrine glands, and teeth. The most characteristic findings are the reduced number of teeth. Any rehabilitative program involves the correct evaluation of skeletal relationships. Implant-prosthodontic treatment can be performed at the end of bone growth. In this paper a case of ED treated with Le Fort I for maxillary advancement, femur homografts, implants€™ insertion and immediate loading is reported. In December 2007, a 38 year-old female was referred to the Maxillofacial Department of Galeazzi Hospital (Milan, Italy) who had a diagnosis of ED. Twelve implants were inserted in one step surgical procedure. To evaluate the clinical outcome several variables (related to anatomy, implant, and prosthesis) were investigated. Implant failure and peri-implant bone resorption were considered as predictors of clinical outcome. Kaplan-Meier algorithm and Cox regression analises were then performed to detect those variables statistically associated with the clinical outcome. The occlusion was stable after 15 months follow-up. No implants were lost. Only one implant has a crestal bone resorption higher than the cut-off value (i.e. one clinical failure over 12 implants, success rate = 91.6%). None of the studied variable has impact on the clinical outcome. In the present case, one step oral rehabilitation was stable in term of occlusion and implant outcome after 15 months. This procedure could be performed in adults with ED, significantly reducing the time of oral and facial rehabilitation.